2017
DOI: 10.1590/2237-6089-2016-0088
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic prescriptions for the treatment of schizophrenia in an outpatient clinic

Abstract: Trends in Psychiatry and Psychotherapy Original ArticleResumo Introdução: Existe um padrão imprevisível na prescrição de antipsicóticos e outros medicamentos psicotrópicos para o tratamento da esquizofrenia, especialmente em ambientes com limitação de recursos em países em desenvolvimento. Objetivo: Determinar as prescrições psicotrópicas dadas a pacientes com esquizofrenia em uma clínica ambulatorial de um hospital terciário e descrever as escolhas e tendências dessas prescrições. Métodos: Este foi um estudo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(26 reference statements)
1
4
0
1
Order By: Relevance
“…A study conducted earlier among same patient population found 67% of the respondents below 40 years of age. 18 Similar findings have also been reported in central India and China. 19,20 However, another crossectional survey among schizophrenia out-patients in a hospital in Nigeria documented that 40% of their respondents were in that age category.…”
Section: Discussionsupporting
confidence: 75%
“…A study conducted earlier among same patient population found 67% of the respondents below 40 years of age. 18 Similar findings have also been reported in central India and China. 19,20 However, another crossectional survey among schizophrenia out-patients in a hospital in Nigeria documented that 40% of their respondents were in that age category.…”
Section: Discussionsupporting
confidence: 75%
“…These results are consistent with the findings in the 2017 study by Oktapaku in Nigeria, which reported that haloperidol was the most widely used antipsychotic among outpatients, and the 2018 study by Khan, which reported that the atypical antipsychotic risperidone was most widely used by patients with schizophrenia. 39,40 The American Psychiatric Association states that the use of different types of antipsychotics depends on the clinical outcome desired. In addition, factors, such as patient response, hospital policy, drug availability, and cost influence the choice of antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…In some parts of the world, there is a higher preference toward the usage of typical antipsychotics, while in other parts of the world, atypical antipsychotics are preferred [ 4 ]. A study pertaining to the drug use pattern of antipsychotics in schizophrenia conducted in the psychiatry outpatient department (OPD) of a tertiary care hospital in Andhra Pradesh showed that olanzapine (37.1%) was the most commonly prescribed antipsychotic [ 5 ], while another study conducted at a tertiary care center in New Delhi showed that risperidone (44.71%) was the most commonly prescribed antipsychotic [ 6 ].…”
Section: Introductionmentioning
confidence: 99%